Diagnóstico do processo de descarte dos resíduos químicos do Hospital Universitário Oswaldo Cruz em Recife/PE - Braga, Lígia de Oliveira (2013)
The waste generation is a current problem and part of human life. The increase of waste grows every day associated with the advancement of technology and industrial production. In this context, are part of the health services, as organizations need to incorporate new concepts to acquire new behaviors in their care processes where issues of environmental preservation and protection of public health need to be highlighted. This challenge has generated public policies and regulations that has assumed great importance as a pillar of sustainable development. These regulations classify healthcare waste generated and have protocols for their management. Within this classification, fall into the chemical waste that is becoming a challenge with regard to the use, disposal and reuse when possible. Thus, this study aims to develop a general diagnosis of the current situation of the management of chemical waste generated at the University Hospital of Pernambuco. Therefore, it was used as the objectives, research is an exploratory-descriptive, as possessing procedure for collecting data literature, field survey, case study and documentary research. The instruments used were the interview guidelines and on-site observation. Given the above and from the survey, we noted the confirmation of the hypotheses on the issues of waste chemicals are not managed according to current legislation, there is no involvement of professionals in planning actions that generate these wastes and that in carrying processes are not taken into account aspects related to the possible chemical waste generated. It can be concluded that although there is a segregation of waste types in the other groups, chemical residues are not treated as such. Needs through the Environmental Education and a new management model train and train practitioners to seek change in the handling of chemical waste. The process of training of professionals and update them need to be continuously and grounded in Environmental Education for the development of new concepts and behavior change that leads to environmental management, considering sustainable development. Why refer to a topic relevant to the issues of environmental and public health, we want to, with the results, cooperate with the academic community showing the problem of chemical waste generated in health services, seeking viable changes to the processes that made generate these wastes, with no loss in quality of care and activities for research.